Produksi VCO Secara Tradisonal sebagai Obat Alami dalam Meningkatkan Pendapatan Masyarakat Desa Watukamba - Marianus Yufrinalis; Henderikus Darwin Beja; Yosef N Tembu Muda; Yosep A Wisang; Ambrosius P Nong; Theresia Y Ercilia; Regina D Gitan (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Virgin Coconut Oil is an oil that is processed from the extraction carried out from fresh coconut fruit which is processed in various ways, one of which is by using traditional methods, namely the natural processing process, namely by photosynthesis. The purpose of making Virgin Coconut Oil is to take advantage of the potential of nature in agriculture in increasing the empowerment of the creative economy of coastal communities during the Covid-19 pandemic. The method used is socialization and training on the process of making Virgin Coconut Oil (VCO). The result obtained is that the people of Watukamba Village realize the importance of utilizing the natural potential in agriculture and being able to produce VCO independently to increase the economic income of the community. The conclusion after community service activities during the pandemic is still felt the benefits by the community and the sustainability of virgin coconut oil (VCO) processing.